Oral cyclodextrin supramolecular for ulcerative colitis treatment through macrophages targeting / ROS response-based accurate on-demand drug release strategy. (February 2023) - Xu, Haiting; Dai, Linxin; Nie, Wenbiao; Luo, Ruifeng; Pu, Xiulan; Dong, Lingling; Chen, Qiyan; Qi, Shanshan; Han, Xiaoqin; You, Jieshu; Zhang, Jinming; Gao, Fei
Graphical abstract: To use the advantages of cyclodextrin (CDs) and overcome their limitations for oral colon-targeted delivery, a rhein-loaded oral CDs supramolecular nanosystem was fabricated based on the physical and chemical properties and structural characteristics of CDs to treat ulcerative colitis (UC). The obtained nanotherapeutics with macrophages targeting / ROS response-based accurate on-demand drug release strategy showed good UC treatment efficacy through anti-inflammatory and antioxidant pathway. Highlights: A cyclodextrin supramolecular system was fabricated for rhein oral delivery against ulcerative colitis. Cyclodextrins-based supramolecular structure can avoid premature drug release in harsh stomach environment. The nanoplatform with macrophages targeting / ROS response-based accurate on-demand drug release strategy could effectively alleviate inflammation. Abstract: Cyclodextrins (CDs) have been applied widely as an oral micro-nano drug delivery material for the treatment of ulcerative colitis (UC) because of their stability around the stomach. However, the further application of CDs is hindered due to their inherent poor targeting and controlled release properties. In this study, CD-supramolecular nanoparticles (HA-CsT@RH) were developed based on the structural characteristics of CDs (e.g., multi-group modifiability and hydrophobic cavity) to encapsulate rhein (RH) for oral delivery against UC. The HA-CsT@RH showed an average size of 154.70 ± 1.80 nm and exhibited high encapsulation efficiency (95.55 ± 2.37 %). When incubated in simulated gastric fluid for 2 h, HA-CsT@RH only released 20.3 ± 0.47 % RH due to the protection of supramolecular effects of CDs. However, RH was rapidly released from HA-CsT@RH (released 66.3 ± 2.50 %) after H2 O2 was treated with the assistance of the ROS-sensitive properties. Moreover, HA-CsT@RH were taken up by macrophages in 1.5 times higher amounts than preparations which did not have CD44-targeted effects. Notably, the results showed that HA-CsT@RH with an accurate on-demand drug release strategy achieved the best anti-inflammatory and antioxidant effects, and they are expected to be a promising carrier in the UC treatment.